Interleukin-10 and Pathogenesis of Murine Ocular Toxoplasmosis - Lu, Fangli (American Society for Microbiology, 2003)
To understand the role of interleukin-10 (IL-10) in ocular toxoplasmosis, we compared C57BL/6 (B6) and BALB/c background mice lacking a functional IL-10 gene (IL-10(−/−)) and B6 transgenic mice expressing IL-10 under the control of the IL-2 promoter. Increased cellular infiltration and necrosis were observed in the eye tissue of IL-10(−/−) mice of both the B6 and BALB/c backgrounds with associated changes in the levels of cytokines in serum. In contrast, there was no evidence of necrosis in the eye tissue from IL-10 transgenic mice following parasite exposure. Our results demonstrate that IL-10 is important in the regulation of inflammation during acute ocular toxoplasmosis.